2011
DOI: 10.1002/aic.12288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ball milling on the hydrolysis of microcrystalline cellulose in hot‐compressed water

Abstract: Ball milling leads to a considerable reduction in cellulose particle size and crystallinity, as well as a significant increase in the specific reactivity of cellulose during hydrolysis in hot‐compressed water (HCW). Cryogenic ball milling for 2 min also results in a significant size reduction but only little change in cellulose crystallinity and specific reactivity during hydrolysis. Therefore, crystallinity is the dominant factor in determining the hydrolysis reactivity of cellulose in HCW while particle size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 39 publications
7
59
0
Order By: Relevance
“…Further, when microcrystalline cellulose was used as substrate sugar yield reduced by half (Fig. 9), which may be attributed to the difficulties associated with getting past the highly packed and crystalline structure of untreated cellulose (crystallinity index ∼82%) [40]. Typically, previous studies have employed amorphous cellulose obtained by ball-milling (48-72 h) as substrate which are much easier to hydrolyze [4,[36][37][38][39][40].…”
Section: Cellulose Hydrolysismentioning
confidence: 98%
“…Further, when microcrystalline cellulose was used as substrate sugar yield reduced by half (Fig. 9), which may be attributed to the difficulties associated with getting past the highly packed and crystalline structure of untreated cellulose (crystallinity index ∼82%) [40]. Typically, previous studies have employed amorphous cellulose obtained by ball-milling (48-72 h) as substrate which are much easier to hydrolyze [4,[36][37][38][39][40].…”
Section: Cellulose Hydrolysismentioning
confidence: 98%
“…Isolation of micro and nanofibrils from various cellulose sources using ball milling methods has already been reported by employing both dry and wet milling conditions (Ago et al 2004;Liimatainen et al 2011;Yu and Wu 2011;Zhang et al 2010). As mentioned earlier, in order to examine the scalability and to identify an optimal processing window, micronizing was performed under wet conditions by systematically varying the milling time and speed.…”
Section: High Energy Ball Millingmentioning
confidence: 99%
“…Cellulose with a lower CrI is more susceptible to hydrolysis because of its loose structure Hendriks and Zeeman 2009). For example, during hydrolysis in hot-compressed water (HCW), the hydrolysis reactions of amorphous cellulose is considerably faster than for crystalline cellulose (Yu and Wu 2011;Yu and Wu 2010). For enzymatic hydrolysis of microcrystalline cellulose, it has also been reported that the lower cellulose CrI, the higher will be the sugar yield and the faster will be the hydrolysis reaction rate (Fan et al 1981;Peng et al 2013;Wang et al 2006).…”
Section: Introductionmentioning
confidence: 99%